2022
DOI: 10.1177/08982643221104926
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Informal and Formal Advance Care Planning Among U.S. Older Adults

Abstract: Objective To examine advance care planning (ACP) trends among an increasingly diverse aging population, we compared informal and formal ACP use by race/ethnicity among U.S. older adults (≤65 years). Methods We used Health and Retirement Study data (2012–2018) to assess relationships between race/ethnicity and ACP type (i.e., no ACP, informal ACP only, formal ACP only, or both ACP types). We reported adjusted risk ratios with 95% confidence intervals. Results Non-Hispanic Black and Hispanic respondents were 1.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…A recent systematic review examined disparities in ACP documentation and found significant differences in rates of completed advanced directives between non‐Hispanic White patients and non‐Hispanic Black patients 11 . Consistent with our findings, other retrospective studies have shown that non‐Hispanic White patients were more likely to have ACP discussions than Latino or African‐American patients 22 . Although recent interventions have utilized EHR‐based tools to improve overall ACP documentation, it is unknown whether these tools were equally applied across various populations as these studies did not stratify their results by race or ethnicity 16,23,24 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A recent systematic review examined disparities in ACP documentation and found significant differences in rates of completed advanced directives between non‐Hispanic White patients and non‐Hispanic Black patients 11 . Consistent with our findings, other retrospective studies have shown that non‐Hispanic White patients were more likely to have ACP discussions than Latino or African‐American patients 22 . Although recent interventions have utilized EHR‐based tools to improve overall ACP documentation, it is unknown whether these tools were equally applied across various populations as these studies did not stratify their results by race or ethnicity 16,23,24 .…”
Section: Discussionsupporting
confidence: 89%
“…11 Consistent with our findings, other retrospective studies have shown that non-Hispanic White patients were more likely to have ACP discussions than Latino or African-American patients. 22 Although recent interventions have utilized EHR-based tools to improve overall ACP documentation, it is unknown whether these tools were equally applied across various populations as these studies did not stratify their results by race or ethnicity. 16,23,24 In contrast to other literature, our study uniquely evaluated the disparate impact of an intervention to improve accessible ACP documentation on patients by race and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative LST documentation rates were significantly lower for Black patients, Hispanic patients, and patients identifying as other (ie, American Indian or Alaskan Native, Asian, Native Hawaiian, or Other Pacific Islander) than for White patients. Although our study focuses on patients undergoing surgical procedures, racial and ethnic disparities in GOC planning have been reported in other studies . Rurality of residence also suggests cultural differences on an individual basis.…”
Section: Discussionmentioning
confidence: 83%
“…Over recent years there has been an increased focus on these disparities, catalysed by factors including the Black Lives Matter movement [12] and the unequal number of deaths during the Covid-19 pandemic [13,14]. Many studies internationally indicate some degree of disparity in rates of ACP related to ethnicity [15][16][17]. Evidence from the USA suggests that White patients have higher rates of hospice use, and formal ACP documentation and/or "do not attempt cardiopulmonary resuscitation" (DNACPR) statements compared with people from other ethnic groups [18][19][20].…”
Section: Race Ethnicity and Acpmentioning
confidence: 99%